Scratch-induced yielding and ductile fracture in silicate glasses probed by nanoindentation - Sawamura, Shigeki; Limbach, Rene; Wilhelmy, Soenke; Koike, Akio; Wondraczek, Lothar (Journal of the American Ceramic Society, 2019)
Lateral nanoindentation provides access to the scratch hardness of glass surfaces. The specific sensitivity of the scratching experiment to surface mechanical properties can be enhanced when the local load at the tip apex is reduced. Here, we report on ramp-load scratch tests on a range of silicate glasses using a sphero-conical tip shape. Similar as with regular scratching experiments using sharp indenters, such tests create a sequence of micro-ductile, micro-cracking, and micro-abrasive regimes. Detailed investigation of the indenter displacement h and of the lateral force FL as recorded in situ, however, reveals pronounced deviations in comparison to Vickers or Berkovich scratching experiments. Most notably, this includes an abrupt increase in both h and FL at moderate normal load, marking the onset of ductile fracture, and a yield point at the transition from fully elastic deformation to the elastic-plastic regime at low load. For the range of examined silicate glasses, we find that structural cohesion controls yielding, whereas scratch-induced fracture and micro-abrasion are dominated by the volume density of bond energy.
CRIS-Team Scopus Importer:2023-04-20
Keywords: glass; hardness; mechanical properties; silicates; soda-lime-silica